The Effect of Mentimeter Learning Media on Students' Learning Outcomes in Biology Learning - Nasution, Muhammad Fahmi; Anas, Nirwana (Universitas Labuhanbatu, 2022)
This research is expected to be able to decide whether the use of a mentimeter has an effect on student learning outcomes in learning biology. The population in this research is third Class (XI) of Mipa 1 with a sample of 30 students as the experimental class and third Class XI of Mipa 2 with a sample of 30 students as the control class. The method in this study uses quantitative methods. The data analysis method was tested with normality test, homogeneity test and Mann-Whitney test then tested the hypothesis with the provisions of Ho; There is no influence of the mentometer on the learning outcomes of students in biology learning. Ha; There is an influence of the mentometer on the learning outcomes of students in learning biology. The results of data analysis were obtained from the normality test with a significance value of not up to 0.05 and a homogeneity test with a value of 0.647 which stated that the data were not normally distributed and not homogeneous. The results of the data from the Mann-Whitney test obtained a result of 0.000 where the results obtained were not up to 0.05 (0.000 <0.05) with the conclusion that the hypothesis was accepted that the mentimeter media affected the learning outcomes of students in biology learning. The conclusion of this study states that the meter basically affects student learning outcomes in learning biology.